Análisis de la velocidad media, media propulsiva y máxima en el gesto del remate sin suspensión del equipo masculino de voleibol de la Universidad de San Buenaventura Medellín - Balbín Londoño, Alejandro (Educación, Ciencias Humanas y Sociales, 2019)
In this study we analyzed the average speed, propulsive average and maximum in the gesture of the auction without suspension of the male volleyball team of the University of San Buenaventura Medellín, the instrument will be given an effective, reliable and validated adaptation, to demonstrate the effect of the technical gesture to evaluate and leave a referent in which the technical gesture is measured in a novel way. A quantitative research was carried out with a descriptive emphasis, which aims to give exact results on volleyball gestures, with the implementation of the instrument. A survey was carried out with 7 multiple-choice questions, the objective of this survey was to know the age, years of experience, frequency of training, which was directed to the male volleyball team where the body mass of 84.1 ± 11, 03; the training frequency 3.2 ± 1.03 and the years of experience with 4 ± 0.81, for the execution of the auction gesture without suspension. It was obtained that maximum acceleration has an average of 141.6, a minimum of 6.29 and a maximum of 199.9, that the average acceleration with an average 0.10, the minimum of 0.003 and a maximum of 0.83. So we reach several conclusions and one of them is that muscle mass apparently directly influences the speed reached at the end, as it could be suggested that, the higher the force, the faster